Comprehensive assessment of the quality of the «pancakes», considering on the norms of the physiological needs of the average person - Kuzmin, Oleg; Krasnoshchokova, Kateryna; Sobutska, Oleksandra; Kuzmenko, Oleksandr; Bezsmertna, Victoriia (My University, 2019)
The method of estimation of the quality of the «pancakes» is considered. The structure of quality indicators and the results of experimental studies of complex quantitative quality assessment are presented. Представлено структуру показників якості та результати експериментальних досліджень комплексної кількісної оцінки якості.
Keywords: quality; pancake; norms of physiological needs of human; якість; панкейк; норми фізіологічних потреб людини; кафедра технології ресторанної і аюрведичної продукції